Procurement design with loss averse bidders - Fugger, Nicolas,Gillen, Philippe,Riehm, Tobias (ZEW - Leibniz Centre for European Economic Research, 2019)
We show that it is beneficial for a buyer to conduct a multi-stage mechanism if bidders are loss averse. In a first step, we derive a revenue equivalence principle. Fixing the multi-stage structure, the revenue is independent of the chosen payment rule. Secondly, we introduce a simple two-stage mechanism which always leads to a decrease in procurement costs compared to any single-stage auction. Finally we derive the optimal efficient two-stage mechanism.
urn:nbn:de:bsz:180-madoc-544990
Keywords: Graue Literatur; Auctions; Experiment; Loss aversion; Preferences